Role of Anterior Neck Soft Tissue Quantifications by Ultrasound in Predicting Difficult Laryngoscopy - Jinhong Wu; Jing Dong; Yingchun Ding; Jijian Zheng (2014)
Background:The aim of this study was to determine if ultrasound (US) measurements of anterior neck soft tissue thickness at hyoid bone (DSHB), thyrohyoid membrane (DSEM), and anterior commissure (DSAC) levels can be used to predict difficult laryngoscopy. Material andMethods:We included 203 patients age 20–65 years scheduled to undergo general anesthesia in this prospective observational study. Correlation analysis and receiver operating characteristic curve (ROC) analysis were used to determine the roles of screening tests [interincisor gap (IIG), thyromental distance (TMD), modified Mallampati score (MMS)] and US measurements (DSHB, DSEM, DSAC) in predicting difficult laryngoscopy. Results:There were 28 out of 203 patients categorized as difficult laryngoscopy. DSHB, DSEM, DSAC, and MMS were greater in the difficult laryngoscopy group (P<0.0001). There was a strong positive correlation between DSEM and DSHB (r=0.74); moderate positive correlations between DSEM and DSAC (r=0.60), DSHB and DSAC (r=0.69); small positive correlations between MMS and DSHB (r=0.32), MMS and DSEM (r=0.27), MMS and DSAC (r=0.32), all P values £0.0001; very small positive correlation between TMD and IIG (r=0.18, P=0.0089); small negative correlation between IIG and MMS (r=–0.27, P=0.0001); and very small negative correlations between MMS and TMD (r=–0.20, P=0.004), IIG and DSAC (r=–0.18, P=0.011), IIG and DSHB (r=–0.15, P=0.034). The areas under the ROC curve (AUCs) of MMS, DSHB, DSEM, and DSAC were significantly larger compared with the reference line (P<0.0001). Conclusions:Anterior neck soft tissue thicknesses measured by US at hyoid bone, thyrohyoid membrane, and anterior commissure levels are independent predictors of difficult laryngoscopy. Combinations of those screening tests or risk factors with US measurements might increase the ability to predict difficult laryngoscopy.